2021
DOI: 10.1101/2021.02.08.430359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep learning for robust and flexible tracking in behavioral studies forC. elegans

Abstract: Robust and accurate behavioral tracking is essential for ethological studies. Common methods for tracking and extracting behavior rely on user adjusted heuristics that can significantly vary across different individuals, environments, and experimental conditions. As a result, they are difficult to implement in large-scale behavioral studies with complex, heterogenous environmental conditions. Recently developed deep-learning methods for object recognition such as Faster R-CNN have advantages in their speed, ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…As a result of this difficulty, the genetic and functional foundations of root phenes are less established than those of aboveground phenes [68,69]. To close this "phenotyping gap," a shift away from traditional phenotyping toward image-based phenotyping has occurred, which enables relatively high throughput while maintaining root measurement accuracy [70]. Numerous platforms make use of two-dimensional imaging via cameras and propagate plants via seedlings on agar plates, germination paper, or fabric cloth in bins [71,72].…”
Section: Root Phenotypingmentioning
confidence: 99%
“…As a result of this difficulty, the genetic and functional foundations of root phenes are less established than those of aboveground phenes [68,69]. To close this "phenotyping gap," a shift away from traditional phenotyping toward image-based phenotyping has occurred, which enables relatively high throughput while maintaining root measurement accuracy [70]. Numerous platforms make use of two-dimensional imaging via cameras and propagate plants via seedlings on agar plates, germination paper, or fabric cloth in bins [71,72].…”
Section: Root Phenotypingmentioning
confidence: 99%
“…Recent studies have shown that machine learning and convolutional neural network (CNN) based approaches can reliably identify worms in variable quality images (Hakim et al, 2018;Bornhorst et al, 2019;Bates et al, 2021). We trained a CNN to differentiate worms from background in 20x20 pixel kernels extracted from our images (see above).…”
Section: Optimization Of Well Preparation and Automated Assessment Of Experiments Qualitymentioning
confidence: 99%
“…Recently, [22,23] used different convolutional neural network models to estimate the physiological age of C. elegans. A method for the identification and detection of C. elegans based on Faster R-CNN was proposed in [24]. Lastly, [25] developed a CNN that classifies young adult worms into short-lived and long-lived.…”
Section: Introductionmentioning
confidence: 99%